Characteristics of water exchange of soybean varieties. - Sulliyeva Suluv Xurramovna; Fozilov Sherzod Musurmonovich (Zien Journals, 2024)
The characteristics of water exchange during the podding phase of different soybean varieties were studied in the soil and climate conditions of Surkhandarya region
Keywords: soybean varieties; growth; development